Teen species - Shephard, Page; British Broadcasting Corporation ([United Kingdom] : BBC Active : BBC Worldwide (distributor), 2006)
This series offers a highly visual insight into the minds and bodies of an extraordinary species ; it tracks teenagers of all ages, classes and cultures and document the changes they experiences; it tracks teenagers over almost two years
episode 1. Girls - episode 2. Boys - episode 3. Adults
Title from title screen
Executive producer, Tessa Livingstone, Alan Bookbinder ; camera, John Howarth...[et al.] ; graphics, Bernard Weyes Design ; editor, John Bognold, Russel Rees
Narrator: Amanda Redman
Keywords: Puberty; Adolescence; Teenagers -- Attitudes; Adolescenct psychology